The Loudness Dependence of Auditory Evoked Potentials (LDAEP) in individuals at risk for developing bipolar disorders and schizophrenia. Issue 2 (February 2016) - Hagenmuller, Florence; Heekeren, Karsten; Meier, Magali; Theodoridou, Anastasia; Walitza, Susanne; Haker, Helene; Rössler, Wulf; Kawohl, Wolfram
Highlights: We examined the Loudness Dependence of Auditory Evoked Potentials (LDAEP) in 187 individuals at risk for bipolar disorders and schizophrenia. We estimated the LDAEP by single electrode estimation and dipole source analysis. Bipolar at-risk subjects showed a weaker LDAEP than schizophrenia at-risk subjects. Abstract: Objectives: The Loudness Dependence of Auditory Evoked Potentials (LDAEP) is considered as an indicator of central serotonergic activity. Alteration of serotonergic neurotransmission was reported in bipolar disorders and schizophrenia. In line with previous reports on clinically manifest disorders, we expected a weaker LDAEP in subjects at risk for bipolar disorders and schizophrenia compared to healthy controls. Methods: We analyzed LDAEP of individuals at risk for developing bipolar disorders ( n  = 27), with high-risk status ( n  = 74) and ultra-high-risk status for schizophrenia ( n  = 86) and healthy controls ( n  = 47). Results: The LDAEP did not differ between subjects at risk for schizophrenia or bipolar disorders and controls. Among subjects without medication ( n  = 122), the at-risk-bipolar group showed a trend towards a weaker LDAEP than both the high-risk and the ultra-high-risk groups for schizophrenia. Conclusions: The LDAEP did not appear as a vulnerability marker for schizophrenia or bipolar disorders. This suggests that an altered LDAEP may not be measurable until the onset of clinically manifest disorder. However, the hypothesis that pathogenic mechanisms leading to bipolar disorders may differ from those leading to schizophrenia is supported. Significance: This is the first study investigating LDAEP in a population at risk for bipolar disorders.